The Relevance of Paid Traffic in B2C Companies: a case study in a microenterprise in the imported products segment - Carlton Ferrarini, Milena; Santos, Thalia dos; Regis, Hayanny Helen Santos (Revista Interface Tecnológica, 2024)
This paper analyzes the relevance of paid traffic and digital marketing strategies for the success of microenterprises, highlighting how these practices can impact sales growth and market visibility. As technologies evolve and consumer demands change, market segmentation becomes crucial for personalizing communications. This study is based on the development of marketing over the years, from Marketing 1.0 to Marketing 5.0, emphasizing the transition from a product-centered focus to an approach that prioritizes consumer experience and the use of technologies such as Artificial Intelligence (AI). The methodology applied was a case study on a company in the imported goods segment that implements digital marketing and paid traffic practices on various digital platforms. The research included a literature review and a qualitative questionnaire to capture the entrepreneurs’ perceptions of the impact of these strategies on sales and lead qualification. The results indicate that paid traffic provides rapid and significant results, reinforcing the importance of good customer relationships. The information gathered allows us to conclude that microenterprises that invest in paid traffic and digital marketing are better positioned to compete and thrive in a constantly evolving environment.